2019
DOI: 10.3389/fgene.2019.00887
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of the SEPT9 Gene Suggests Significantly Poor Prognosis in Cancer Patients: A Systematic Review and Meta-Analysis

Abstract: Background: Aberrant hypermethylation of the Septin 9 (SEPT9) is an early event in several human cancers, and increasing studies have reported good performance of methylated SEPT9 (mSEPT9) in cancer diagnosis. Recent studies further focused on its value in cancer prognosis, but results are not clearly elucidated.Methods: A comprehensive search to identify relevant studies about the association between mSEPT9 and cancer prognosis was conducted through the EMBASE, PubMed, and Web of Science databases (up to Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…The mSEPT9 has been demonstrated to be an independent risk factor and can predict the long-term survival of both CRC and HCC. 9 , 30 , 31 In the present study, we demonstrated that this assay is an independent factor and predictive marker for long-term survival for all four types of digestive cancers. Predictions based on dichotomized pre-therapeutic mSEPT9 interpretation suggested that patients with digestive cancer who had undetectable levels of mSEPT9 in their blood prior to therapy would generally exhibit significantly better survival rates than those with detectable levels of mSEPT9 in their blood.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The mSEPT9 has been demonstrated to be an independent risk factor and can predict the long-term survival of both CRC and HCC. 9 , 30 , 31 In the present study, we demonstrated that this assay is an independent factor and predictive marker for long-term survival for all four types of digestive cancers. Predictions based on dichotomized pre-therapeutic mSEPT9 interpretation suggested that patients with digestive cancer who had undetectable levels of mSEPT9 in their blood prior to therapy would generally exhibit significantly better survival rates than those with detectable levels of mSEPT9 in their blood.…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, this marker has been shown to be effective in a variety of applications for CRC, including the screening of average-risk populations, 1 opportunistic screening, 3 , 4 the monitoring of therapeutic effects in surgery, 30 the monitoring of therapeutic effects during late-stage CRC, 31 and the prediction of therapeutic effects and long-term survival in patients with CRC. 30 , 31 However, it should be noted that the prediction of survival by mSEPT9 was largely dependent on cancer stage, and that patients with advanced stages of cancer have higher levels of mSEPT9 in their blood; consequently, these patients are more likely to test positive and have a worse prognosis than those with early stages. Therefore, our stratification of survival by stage clearly showed that the marker may be predictable for the long-term survival of stage III–IV patients but not predictable for stage I–II patients under the current study design and follow-up duration.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological phenotype of rightsided colon cancer is poor differentiation, high proportion of advanced disease, increased mucinous adenocarcinoma, and high propensity for complications and second primary intestinal tumor that associates with poor prognosis (Missiaglia et al, 2014;Sveen et al, 2019). Further, a previous study observed differences in the positive rate of SEPT9 methylation in the peripheral blood of CRC patients with varied clinicopathological characteristics, and its positive rate is significantly related to the malignant biological behavior (Shen et al, 2019). Our previous studies showed that the methylation of SEPT9 is associated with the TNM stage, total tumor volume, and mismatch repair deficient status (Sun et al, 2019), suggesting that mSEPT9 in peripheral blood may be related with the pathological stage and the prognosis of patients.…”
Section: Discussionmentioning
confidence: 97%
“…However, the influence of CIMP on the drug efficacy is still unclear. At present, studies about mSEPT9 mainly focus on screening, diagnosis, prognosis, and correlation analysis with histopathology, and Shen N et al reported that the hypermethylation of SEPT9 associated with worse overall survival (OS) and disease-free survival (DFS) ( Shen et al, 2019 ), but there were no systematic reports about the relationship between mSEPT9 with specific molecular characteristics of CRC and the prognosis value of adjuvant chemotherapy or recurrence. Our previous study showed that mSEPT9 is related to the TNM stage, Dukes stage, and dMMR status of CRC ( Sun et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…ЭКСПЕРИМЕНТАЛЬНЫЕ СТАТЬИ ТОМ 6 / VOL. 6 желудка, предстательной железы, вне-и внутрипеченочных желчных протоков [11].…”
Section: Al Identification Of a New Methylation Site In The Sept9 Prunclassified